Panel data analysis of the proposed monetary union in the Southern African development community - Mulatu Fekadu Zerihun; Marthinus C. Breitenbach (SPOUDAI - Journal of Economics and Business, 2017)
This paper examines the sensibility of a proposed monetary union in the Southern African Development Community (SADC). The study hypothesizes that the majority of the economies in the SADC region are candidates for a monetary union. We test this hypothesis against one of the prime optimal currency area (OCA) theory criteria, namely economic homogeneity with reference to real exchange rates. The quantitative analysis encompasses monthly data of 11 SADC member countries over the period 1995-2016. We use first and second generation panel unit root tests and panel cointegration tests to test mainly for stationarity and cointegration of real exchange rate series for the group of SADC countries. The findings from this study confirm that there is stationarity and cointegration of the real exchange rate series among the 11 SADC member countries included in this study. These countries can be potential candidates to form the proposed monetary union in the SADC region. Economic homogeneity i.e. economies with common structural and institutional characteristics, is one of the requirements to be fulfilled prior to joining monetary union. It reduces the impact of asymmetric shocks to a group of countries forming a monetary union. Economic homogeneity is observed where real exchange rates of countries tend to move together and mean-reversion behavior reveals how well real exchange rates adjust back to equilibrium after experiencing an asymmetric shock. This result has important policy implications for the proposed monetary union in the SADC region.
Keywords: C32; E31; F15; F41; 330; Optimum Currency Area; Monetary Union; Real Exchange Rate; Panel Cointegration; Panel Unit Root test